The identification, assessment and implications of an organization's learning system for the practice of adult education in organizational settings - Dent C. Davis; Mary F. Ziegler (Adult Education Research Conference, 1995)
Traditional approaches to adult learning in organizational settings concentrate on the individual rather than the organizational setting. This study focused on the organizational context for adult learning in the workplace. We present the background that led up to the study, the purpose of the research, the conceptual framework, the methodology and findings. Implications for practice and research conclude the article.